A case report on MDS – MPD overlap syndrome – a diagnostic dilemma - Dr Anita Omhare; Dr Sanjeev Kumar Singh; Dr Kanchan Srivastava; Dr Vandana Mishra; Shilpa U. Vahikar (Tropical Journal of Pathology and Microbiology, 2017)
Refractory anemia with ring sideroblasts and thrombocytosis (RARS - T) is a rare disease with a controversial status which presents a diagnostic dilemma as it shows overlapping clinical, laboratory and morphological features of two distinct entities-myelodysplastic syndrome (MDS) and myeloproliferative neoplasms (MPN). In WHO classification RARS–T is included in MDS/MPN–U category. We report a case of 54 years female who presented with weakness, intermittent fever, anemia along with thrombocytosis. Hematological workup revealed hypercellular marrow with abnormal megakaryocytes and presence of ring sideroblasts (46%). Further, presence of JAK2V617F mutation indicated an underlying MPN and presence of ring sideroblasts an element of MDS. RARS-T was first defined in 2001 as an overlap syndrome. Whether RARS-T is a separate clinical entity or a result of additional acquired genetic defect resulting in progression of RARS/ Essential Thrombocytosis (ET) is still a topic for debate. Hence this unusual case emphasizes need for awareness of this entity among clinicians and pathologists to enable its accurate diagnosis and appropriate management.